Removal of ammonia from anaerobic co-digestion effluent of organic fraction of food waste and domestic wastewater using air stripping process - Lan Huong Nguyen; Hong Ha Bui; Xuan Truong Nguyen (Vietnam Journal of Science, Technology and Engineering, 2020)
In this study, a continuous ammonium stripping lab-scale model of anaerobic co-digestion effluent from an organic fraction of food waste and domestic wastewater was used to investigate ammonium removal efficiency by air stripping. The effect of initial pH, liquid flow rate, and air-to-liquid ratio on the removal of ammonium from the effluent were examined in experiments. The operating parameters of the trials were established based on calculations from influent and effluent ammonia concentration and the theory of mass transfer. The results indicated that a pH value of 11, liquid flow of 0.25 l/min, and a ratio of air-to-liquid of 2925 gave a >90% ammonia removal efficiency and thus reached the allowable ammonia levels of wastewater discharged into receiving sources. The continuous stripping of nitrogen from anaerobic co-digestion of effluent had a huge significance in the removal of ammonium and recovery of ammonia gas , which aids in eutrophication prevention and fertilizer production.